PEDAGANG MIRAS GEROBAK DORONG (STUDI KASUS TENTANG PENGAWASAN SOSIAL TERHADAP PEDAGANG MIRAS GEROBAK DORONG) DI JALAN JUANDA PEKANBARU - Muhammad Iqbal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted Jalan Juanda Pekanbaru. The purpose of this study was to determine how the activity of selling liquor juanda streets. This study, entitled "Alcohol Traders Push Carts (Case Study On Social Monitoring Against Alcohol Traders Push Carts) In Jalan Juanda Pekanbaru". Topics focus of this research is how the activity of selling liquor on the street juanda pekanbaru. The sample of this study was the hawkers on the street juanda. Samples are numbered 6 people head hawkers author uses descriptive qualitative method and the data were analyzed qualitatively. Instrument Data is observation, interviews, questionnaires and documentation. The results showed that the activity of selling alcoholic drinks in the evening which starts at 18.00 AM to 06.00 AM. Activity liquor trade was deliberately done at night because customers usually consume liquor at night, and also because at night the younger perform this transaction liquor trade. The survey results revealed that the liquor trade is long-standing in the way juanda. liquor is traded known from overseas like Singapore. liquor obtained through duku river port with intermediaries such liquor sales agent. During raids conducted liquor traders are not too worried, because they've been told by people in that they pay for member news when liquor is held by the authorities.Keywords: Alcohol, Alcohol Trading Activity